PENGARUH KESADARAN LINGKUNGAN DAN NILAI PELANGGAN TERHADAP NIAT BELI ULANG BERAS ORGANIK PADA KONSUMEN WANITA DI SURABAYA - Setyadarma, Bambang; Prayitno, Budi (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2012)
The purpose of this study was to prove the influence of environmental awareness and the customer value toward repurchase intention of organic rice. The population in these research were all the consumers who buy organic rice in Surabaya, while the sampling technique used in this study was purposive sampling. The sample criterion were women in age over 25 years, had married and had bought organic rice. The sample size were 100 women as buyers of organic rice in 10 hypermarkets and 1 supermarkets in Surabaya. Testing the hypothesis in this study using multiple linear regression that was used to examine the effect of environmental awareness and customer value on repurchase intention of organic rice.The result of multiple linear regression indicated that environmental awareness (X1) and customer value (X2) had impact on repurchase intention (Y).